2018
DOI: 10.1002/ange.201712469
|View full text |Cite
|
Sign up to set email alerts
|

Kohlenstoff‐Nanozyme: Enzymatische Eigenschaften, Katalysemechanismen und Anwendungen

Abstract: Nanozyme haben spezifische Vorteile gegenüber natürlichen Enzymen, wie ihre einfache Produktion in großen Mengen, lange Lagerzeiten, niedrige Kosten und hohe Stabilität unter harschen Umgebungen. Kohlenstoffnanomaterialien (CNMs), einschließlich Fullerenen, Kohlenstoffnanoröhren, Graphen, Kohlenstoffquantenpunkten und Graphenquantenpunkten, sind zu einer herausragenden Substanzfamilie in den Materialwissenschaften geworden. Über die katalytischen Aktivitäten von CNMs und ihren Hybridverbindungen als eine neue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 176 publications
(456 reference statements)
0
6
0
Order By: Relevance
“…[57] Grapheneq uantum dots (GQDs), as zero-dimensional derivatives of GMs, have similar peroxidase-mimicking properties and consequently are used to induce the antibacteriala ctivity of H 2 O 2 at low concentrations. [58,59] It was revealed that -C=O groups are the catalytically active sites and O=CÀO-groups are the substrate-binding sites of GQDs, whereas the -CÀOH groups can inhibit the antibacterial activity of the materials. [60] In addition, although GMs have inherenta ntimicrobial activity,t heir efficacy needs to be improved further for practical applications.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 99%
“…[57] Grapheneq uantum dots (GQDs), as zero-dimensional derivatives of GMs, have similar peroxidase-mimicking properties and consequently are used to induce the antibacteriala ctivity of H 2 O 2 at low concentrations. [58,59] It was revealed that -C=O groups are the catalytically active sites and O=CÀO-groups are the substrate-binding sites of GQDs, whereas the -CÀOH groups can inhibit the antibacterial activity of the materials. [60] In addition, although GMs have inherenta ntimicrobial activity,t heir efficacy needs to be improved further for practical applications.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 99%
“…Mimicking the enzyme's bioactivity utilizing nanomaterials, also named as nanozymes, is an efficient means to extend the biocatalysis in a cell‐free environment [10–12] . Up till now, metallic oxides, [11, 13] doped carbon, [14] single‐atomic metal catalysts [15, 16] and metal–organic frameworks (MOFs) [10, 17] have been constructed as the desirable nanozymes with oxidase [18, 19] ‐, peroxidase [20] ‐, catalase [21] ‐, superoxide [22] ‐ and hydrolase [21, 23] ‐like activities. Indeed, these nanozymes well circumvent the structural susceptibility of natural enzymes, and also improve the efficiencies in recovery and reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the characteristics of low cost, high stability and excellent repeatability, artificial mimic enzymes have been widely explored for their great potential application ranging from medicine, food processing, environmental analysis, and biotechnology [1] . Various nanozymes have been verified to possess good peroxidase activity, such as metal oxides, [2] noble metal, [3] carbon nanomaterials, [4] metal‐organic frameworks [5] . The catalytic property of mimic enzymes is directly affected by composition, structure and morphology of nanomaterials [6] .…”
Section: Introductionmentioning
confidence: 99%